Clinical outcomes of COVID-19 in patients undergoing chronic hemodialysis and peritoneal dialysis - Gorayeb-Polacchini,Fernanda Salomão (2022)
Abstract Background: The reported incidence and fatality rate of the severe acute respiratory syndrome coronavirus 2 in patients receiving chronic dialysis are higher than in the general population. We sought to study the outcomes following coronavirus disease 2019 (COVID-19) diagnosis in patients undergoing chronic hemodialysis (HD) or peritoneal dialysis (PD) in a single center in Brazil. Methods: Of the 522 patients on dialysis evaluated between March 1, 2020, and October 1, 2021, those presenting symptoms or with a history of close contact with COVID-19 patients were tested with reverse-transcription polymerase chain reaction of samples from nasopharyngeal swabs. Results: Of the 522 patients, 120 were positive for COVID-19 infection, of which 86% were on HD and 14% in the PD program. The incidence per 10,000 inhabitants was higher in the HD group than in the PD group (2,423.5 vs. 1,752.5). The mortality per 10,000 inhabitants (470.5 vs. 927.8) and the fatality rate (19.4 vs. 52.9%, p = 0.005) were higher in the PD group. The PD group also had a higher need for hospitalization, intensive care, and mechanical ventilation. Conclusions: We advise caution when considering strategies to transfer patients from HD to the PD program to minimize the risk of COVID-19 for patients on HD.